Publishing at any cost: a cross-sectional study of the amount that medical researchers spend on open access publishing each year - Mallory K. Ellingson; Xiaoting Shi; Joshua J. Skydel; Kate Nyhan; Richard Lehman; Joseph S. Ross; Joshua D. Wallach (BMJ Open)
Objective To estimate the financial costs paid by individual medical researchers from meeting the article processing charges (APCs) levied by open access journals in 2019.Design Cross-sectional analysis.Data sources Scopus was used to generate two random samples of researchers, the first with a senior author article indexed in the ‘Medicine’ subject area (general researchers) and the second with an article published in the ten highest-impact factor general clinical medicine journals (high-impact researchers) in 2019. For each researcher, Scopus was used to identify all first and senior author original research or review articles published in 2019. Data were obtained from Scopus, institutional profiles, Journal Citation Reports, publisher databases, the Directory of Open Access Journals, and individual journal websites.Main outcome measures Median APCs paid by general and high-impact researchers for all first and senior author research and review articles published in 2019.Results There were 241 general and 246 high-impact researchers identified as eligible for our study. In 2019, the general and high-impact researchers published a total of 914 (median 2, IQR 1–5) and 1471 (4, 2–8) first or senior author research or review articles, respectively. 42% (384/914) of the articles from the general researchers and 29% (428/1471) of the articles from the high-impact medical researchers were published in fully open access journals. The median total APCs paid by general researchers in 2019 was US$191 (US$0–US$2500) and the median total paid by high-impact researchers was US$2900 (US$0–US$5465); the maximum paid by a single researcher in total APCs was US$30115 and US$34676, respectively.Conclusions Medical researchers in 2019 were found to have paid between US$0 and US$34676 in total APCs. As journals with APCs become more common, it is important to continue to evaluate the potential cost to researchers, especially on individuals who may not have the funding or institutional resources to cover these costs.